The rise of harmful cyanobacteria blooms: The potential roles of eutrophication and climate change - O’Neil, J.M.; Davis, T.W.; Burford, M.A.; Gobler, C.J. (Harmful algae, 2012)
Cyanobacteria are the most ancient phytoplankton on the planet and form harmful algal blooms in freshwater, estuarine, and marine ecosystems. Recent research suggests that eutrophication and climate change are two processes that may promote the proliferation and expansion of cyanobacterial harmful algal blooms. In this review, we specifically examine the relationships between eutrophication, climate change and representative cyanobacterial genera from freshwater ( Microcystis, Anabaena, Cylindrospermopsis), estuarine ( Nodularia, Aphanizomenon), and marine ecosystems ( Lyngbya, Synechococcus, Trichodesmium). Commonalities among cyanobacterial genera include being highly competitive for low concentrations of inorganic P (DIP) and the ability to acquire organic P compounds. Both diazotrophic (= nitrogen (N 2) fixers) and non-diazotrophic cyanobacteria display great flexibility in the N sources they exploit to form blooms. Hence, while some cyanobacterial blooms are associated with eutrophication, several form blooms when concentrations of inorganic N and P are low. Cyanobacteria dominate phytoplankton assemblages under higher temperatures due to both physiological (e.g. more rapid growth) and physical factors (e.g. enhanced stratification), with individual species showing different temperature optima. Significantly less is known regarding how increasing carbon dioxide (CO 2) concentrations will affect cyanobacteria, although some evidence suggests several genera of cyanobacteria are well-suited to bloom under low concentrations of CO 2. While the interactive effects of future eutrophication and climate change on harmful cyanobacterial blooms are complex, much of the current knowledge suggests these processes are likely to enhance the magnitude and frequency of these events.